Subsurface resistivity and implications for groundwater potentials in parts of Etche, Rivers State, Nigeria - Eke, Peter Ogochuku; Worgu, Bright; Ziriki, Godwill (Faculty of Natural and Applied Sciences Journal of Scientific Innovations, 2023)
This study determines the groundwater potentials of parts of Etche using the vertical electrical sounding (VES) method. The resistivity of subsurface formations can be interpreted to obtain aquifer characteristics and infer the groundwater potentials of a region. Etche in Rivers State, Nigeria, has urban cities that are developing every day with an increasing need for domestic water use. This study determines the groundwater potentials of parts of Etche using the vertical electrical sounding (VES) method. Twenty-three (23) vertical electrical soundings were carried out with locations in Akpoku, Chokocho, Elele, Ikwerrengwo, Obite, Odagwa, Okehi, Okomoko, Orwu, Ozuzu, Ulakwo, Umuakuru, Umualikpo, Umuanyagu, Umuasukpo, Umuazu, Umuebulu, Umuogodo, Umuokwa, Umuokwanukwu, Umuometa, Umutube, and Umuoye, all in Etche, using ABEM (SAS) 4000 Terrameter. The Schlumberger electrode configuration, with a maximum electrode spacing of 500 m was used. The apparent resistivity values obtained were plotted against half the current spread in IPI2WIN software to obtain the curve types, formation true resistivities, the geoelectric layers, formation thickness and depths. These were analyzed to obtain aquifer depths, thickness, transverse resistivity, longitudinal conductance, transmissivity and storativity of the region. From the results, the curve types are mostly A, K, B and KH curves. The resistivity values range from 405 Ω in Chokocho to 4985.6 Ω in Odagwa, with an average value of 2314.8 Ω for the surveyed areas. Aquifer thickness ranges from 8.2 m in Orwu to 97 m in Umuokawnukwu with an average of 47.5 m for the area. The average aquifer depth for the region is 59.1 m, with Orwu having 10.8 m and Umuokwanukwu having 105 m. Transverse resistivity values range from 12775.6 Ωm2 in Orwu to 176477.1 Ωm2 in Umuaskpo and an average value of 103220.2 Ωm2 for the region. Longitudinal conductance range from 0.00437 Ω-1in Odagwa to 0.14321 Ω-1 in Chokocho with the region having an average value of 0.3093 Ω-1. Transmissivity values range from 235338.7 m2/day in Umuebubu to 127756.6 m2/day in Orwu and an average value of 103220.2 m2/day in the study area. Storativity values range from 1.07 x 10-5 in Orwu to 9.82 x 10-5 in Okomoko with an average value of 1.9 x 10-5 for the region. These results reveal that aquifer characteristics in the study area show potential for groundwaterreservoirs with the eastern part of the region being more prolific. Generally, the groundwater potential in theregion is good based on the storativity and transmissivity values and boreholes can be drilled at depths of 20 m inmost of the areas to obtain drinkable groundwater.